2022
DOI: 10.1002/jper.22-0120
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of biologics for the treatment of periodontal infrabony defects: An American Academy of Periodontology best evidence systematic review and network meta‐analysis

Abstract: Background: A large variety of biomaterials, biologics and membranes have been utilized in the past 40 years for the regenerative treatment of periodontal infrabony defects. Biologic agents have progressively gained popularity among clinicians and are routinely used for periodontal regeneration. In alignment with the goals of the American Academy of Periodontology (AAP) Best Evidence Consensus (BEC) on the use of biologic mediators in contemporary clinical practice, the aim of this sytematic review was to eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(50 citation statements)
references
References 212 publications
2
39
0
Order By: Relevance
“…The pairwise meta‐analysis studies 8 showed that PRF provided comparable clinical effects to bone grafts or enamel matrix derivative (EMD), which was also in line with this review. Contrary to our study, previous meta‐analysis 33 showed that PRF demonstrated higher radiographic bone gain ( p < 0.05) than EMD in the treatment of intrabony defects whereas PRF provided a comparable effect to EMD in clinical attachment level gain and probing pocket depth reduction ( p > 0.05), 33 which in line with our current NMA.…”
Section: Discussionsupporting
confidence: 85%
“…The pairwise meta‐analysis studies 8 showed that PRF provided comparable clinical effects to bone grafts or enamel matrix derivative (EMD), which was also in line with this review. Contrary to our study, previous meta‐analysis 33 showed that PRF demonstrated higher radiographic bone gain ( p < 0.05) than EMD in the treatment of intrabony defects whereas PRF provided a comparable effect to EMD in clinical attachment level gain and probing pocket depth reduction ( p > 0.05), 33 which in line with our current NMA.…”
Section: Discussionsupporting
confidence: 85%
“…According to current available evidence and within the limitations of a systematic review prepared prior to the consensus conference, the following conclusions can be drawn from the frequentist mixed‐modeling approach to network meta‐analysis: 13 The use of biologics (i.e., ABPs, EMD, and rhPDGF‐BB) may significantly enhance the clinical and radiographic outcomes after the surgical treatment of infrabony defects. rhPDGF‐BB and PRF are associated with superior clinical and radiographic outcomes compared to EMD and platelet‐rich plasma (PRP). Combination therapies involving bone grafts, either with a biologic or barrier membrane, are the most effective strategies for the treatment of infrabony defects. However, the use of membranes with biologics should be avoided when graft containment is feasible since their combined use may prevent some of the benefits associated with the use of biologics (i.e., chemotaxis for pluripotential mesenchymal cell migration from soft tissue niches). Allogeneic and xenogeneic bone grafts are associated with greater clinical benefits regarding clinical outcomes than autogenous and synthetic bone grafts. Xenogeneic bone grafts with rhPDGF‐BB or PRF are the best combination therapy to maintain the stability of the gingival margin following regenerative treatment of periodontal infrabony defects. …”
Section: Focused Clinical Questionmentioning
confidence: 99%
“…According to current available evidence and within the limitations of a systematic review prepared prior to the consensus conference, the following conclusions can be drawn from the frequentist mixed‐modeling approach to network meta‐analysis: 13 The use of biologics (i.e., ABPs, EMD, and rhPDGF‐BB) may significantly enhance the clinical and radiographic outcomes after the surgical treatment of infrabony defects. rhPDGF‐BB and PRF are associated with superior clinical and radiographic outcomes compared to EMD and platelet‐rich plasma (PRP).…”
Section: Focused Clinical Questionmentioning
confidence: 99%
“…Evidence quality rating and strength of recommendation of STA procedures at implant sites were assessed in terms of levels of certainty in the body of evidence, net benefit rating (benefit‐harm estimation), and strength of recommendation, as previously described (Avila‐Ortiz et al, 2022; Tavelli, Chen, Barootchi, & Kim, 2022). Additional information are depicted in the Appendix S1.…”
Section: Methodsmentioning
confidence: 99%